PROSPECTS OF INTERSTATE COOPERATION: SOUTH KOREAN AND UKRAINIAN BIOINDUSTRY - Domashovets, Anhelina; Shved, Olha (Collection of scientific papers «ΛΌГOΣ», 2025)
One of the fastest-growing and most promising sectors of the modern economy is the bioindustry, which is rapidly advancing in leading countries through investments in science, innovation, and green technologies. It plays a crucial role in promoting sustainable development by decreasing reliance on fossil fuels, preserving the environment, and generating new high-tech jobs, thereby strengthening economic resilience and boosting global competitiveness.